Stroke survivors' recommendations for the visual representation of movement analysis measures: a technical report. Issue Volume 107:Issue (2020) (June 2020) - Lane, Kathleen; Chandler, Elizabeth; Payne, David; Pomeroy, Valerie M.
Abstract: Background: Stroke survivors do not have routine access to objective feedback on their movement performance. Objective: To devise visual representation of objective measures of movement performance that are understandable by and meaningful to stroke survivors. Design: Co-production through interviews and generative discussion. Participants: Eight people, mean age 65 years, who were at least one year after stroke with low, medium or high functional ability. All provided informed consent. Data collection: Participants performed standardised upper and lower limb functional tasks. Their movement was measured using the Vicon motion analysis system and surface electromyography. Participants returned six months later when they were shown anonymised visual representations of the movement tasks. Nobody saw their own data. Visual representations were provided of people with low, medium and high functional ability. A generative discussion elicited participants' views on how the measures should be presented visually to maximise understandability and meaningfulness. Findings: Participants' understanding of the visual presentation of movement analysis was enhanced with the addition of everyday symbols such as a stick-figure and a brief explanation from a physiotherapist/researcher. Meaningfulness was seen in terms of motivation to participate in and ownership of their rehabilitation. Implications: These findings justify further development of objective measures of movement performance for use in routine clinical practice.